From Work to Home: The Psychological Impact of an Always-On Culture - Dewi Yullianty; Aryana Satrya (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The study aims to analyze the effect of Work Connectivity Behavior After Hours (WCBA) on Work Stress (WS), Work-Family Conflict (WFC), and Psychological Distress (PD) among civil servants in a public sector institution responsible for managing the commercial sector. A cross-sectional design was employed, with 357 responses analyzed using the CB-SEM approach. The findings indicate that WCBA significantly influences work stress and work-family conflict, both of which, in turn, directly affect psychological distress. Moreover, work stress and work-family conflict significantly mediate the relationship between WCBA and psychological distress. These results highlight the need for public sector institutions to implement the right-to-disconnect principle to protect employees’ psychological well-being and reduce work-related stress and conflict.